(untitled) (TAMADDUN NURI JURNALI, 2024)
This article scientifically analyzes opinions on the professional spirituality of civil servants in the hierarchy “person – society – state”. Also, when implementing the relationship “Man – Society – State”, special attention is paid to issues closely related to personnel policy, training and support of qualified personnel for the provision of public civil service.